Hospital Pedagogy: Knowing its modalities of attendance (Research, Society and Development, 2017)
The present study presents a field in which the pedagogue can exercise outside of the school environment: the area of the hospital pedagogy, in which it is within the special education. It has as justification to extend the knowledge and the divulgation of the treated area, thus contributing to the aim of this study was to understand and deepen our studies about the modalities of pedagogical assistance existing in hospital environments. The methodology used was the bibliographic review. We discuss in this study that the function of hospital pedagogy is to provide hospitalized children and adolescents with adequate care, where they feel well attended and welcomed, since the hospital environment is different from their reality. In this context, it is necessary that there are professionals prepared and adequately trained to act. The adequate training of this pedagogue allows him to act in a coherent way within the existing modalities in the hospital scope, in which three of them stand out: bed attendance, hospital class and toy library. We consider it relevant to emphasize that hospital pedagogy is not known to all, and it is necessary to have a greater dissemination of its importance for awareness.